Development of a Specialized Method for Simultaneous Quantification of Functional Intestinal Metabolites by GC/MS-Based Metabolomics - Kazuki Funahashi; Chol Gyu Lee; Kuniyo Sugitate; Noriko Kagata; Noriko Fukuda; Isaiah Song; Chiharu Ishii; Akiyoshi Hirayama; Shinji Fukuda (Gut Microbes Reports)
Intestinal metabolites produced by gut microbes play a significant role in host health. Due to their different chemical structures, they are often analyzed using multiple analyzers and methods, such as gas chromatography/mass spectrometry (GC/MS) for SCFAs and liquid chromatography/mass spectrometry (LC/MS) for bile acids (BAs), amino acids (AAs), and sugars. In this study, we aimed to develop a specialized method for the simultaneous determination of important intestinal metabolites, specifically addressing the main issue of SCFA volatilization during the dry solidification process. We discovered that these compounds can all be measured in fecal samples by GC/MS after trimethylsilyl (TMS) derivatization despite the expected volatility of SCFAs. Validating the results using SCFA standards suggested that the fecal matrix exerts a stabilizing effect. This method enabled the simultaneous quantification of 65 metabolites. For further validation in a biological context, a mouse study showed that high-MAC and high-fat diets increased SCFAs and BAs in feces, respectively, and showed a negative correlation between Alistipes and sugars, all consistent with previous studies. As a result, we successfully developed a specialized simultaneous quantification method for SCFAs, BAs, AAs, AA derivatives, and sugars in fecal samples using GC/MS-based metabolomics in conjunction with a TMS derivatization pretreatment process.